Reconfiguring institutions across time and space : syncretic responses to challenges of political and economic transformation - Galvan, Dennis Charles; Sil, Rudra, 1967- (Political evolution and institutional change., 2007)
This volume explores the unanticipated consequences of emulating, importing, or imposing new institutional models without commensurate attention to the particular constellations of interests, identities, norms, and social relations embedded in local communities. Each chapter is organized around a common problematic that has received only limited attention in the literature on institutional change: the dilemmas of deploying the rules, practices, and design of institutions that have been imported or imposed from external environments in regions where actors are more familiar with and find more legitimate locally embedded norms, practices, social relations, and knowledge structures. The volume strives to illustrate the analytic power of the concept of ¿syncretism, ¿ a concept that can be fruitfully deployed to analyze common aspects of institutional change not easily captured in existing frameworks.